Speech by Brig. Gen. Dato' Prof. Dr. Kamarudin Hussin Vice Chancellor of UniMAP for Opening Ceremony Micotribe Conference - Kamarudin, Hussin, Brig. Gen. Dato' Prof. Dr. (Universiti Malaysia Perlis, 2010)
Majlis berlangsung di PWTC, Kuala Lumpur.